Polymerization of a Photocleavable Monomer Using Visible Light. Issue 11 (28th April 2016) - Bagheri, Ali; Yeow, Jonathan; Arandiyan, Hamidreza; Xu, Jiangtao; Boyer, Cyrille; Lim, May
Abstract : The polymerization of the photocleavable monomer, o ‐nitrobenzyl methacrylate (NBMA), is investigated using photoinduced electron/energy transfer reversible addition‐fragmentation chain transfer polymerization. The polymerizations under visible red ( λ max = 635 nm, 0.7 mW cm −2 ) and yellow ( λ max = 560 nm, 9.7 mW cm −2 ) light are performed and demonstrate rational evidence of a controlled/living radical polymerization process. Well‐defined poly( o ‐nitrobenzyl methacrylate) (PNBMA) homopolymers with good control over the molecular weight and polymer dispersity are successfully synthesized by varying the irradiation time and/or targeted degree of polymerization. Chain extension of a poly(oligo(ethylene glycol) methyl ether methacrylate) macro‐chain transfer agent with NBMA is carried out to fabricate photocleavable amphiphilic block copolymers (BCP). Finally, these self‐assembled BCP rapidly dissemble under UV light suggesting the photoresponsive character of NBMA is not altered during the polymerization under yellow or red light. Such photoresponsive polymers can be potentially used for the remote‐controlled delivery of therapeutic compounds. Abstract : The facile synthesis of low dispersity photocleavable polymers are demonstrated for the first time using a novel photopolymerization approach. Under a visible light stimulus (530–655 nm), poly( o ‐nitrobenzyl methacrylate) polymers are readily synthesized using a metal‐based or organic photoredox catalyst with good polymerization control.